2014
DOI: 10.7314/apjcp.2014.15.22.10015
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Increases Colorectal Carcinoma Cell Apoptosis by Inhibition of NF-κB in a Sirt1-dependent Manner

Abstract: Background: Fentanyl is used as an analgesic to treat pain in a variety of patients with cancer and recently it has become considered to also act as an antitumor agent. The study present was designed to investigate the effects of fentanyl on colorectal cancer cell growth and plausible mechanisms. Materials and Methods: The human colorectal carcinoma cell line HCT116 was subcutaneously injected into nude mice. The viability of HCT116 was tested by MTT assay, and apoptosis by flow cytometry and caspase-3 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Moreover, MOR has been reported to play a crucial role in the fundamental cellular epithelial mesenchymal transition changes that occur during lung cancer progression [21]. This study supported the antitumor role of fentanyl in CRC progress, in which inhibiting the invasion and migration of CRC cells in vitro, as well as cell clonal formation, in line with reports about other CRC cell lines with fentanyl treatment [6,7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, MOR has been reported to play a crucial role in the fundamental cellular epithelial mesenchymal transition changes that occur during lung cancer progression [21]. This study supported the antitumor role of fentanyl in CRC progress, in which inhibiting the invasion and migration of CRC cells in vitro, as well as cell clonal formation, in line with reports about other CRC cell lines with fentanyl treatment [6,7].…”
Section: Discussionsupporting
confidence: 90%
“…Since studies have indicated some other effects of fentanyl on CRC cells [6,7], including cell viability, cell migration and invasion, the negative regulation of Ets-1 on BANCR expression was further Fig. 2.…”
Section: Co-overexpressed Bancr Reversed the Effects Of Ets-1 Overexpmentioning
confidence: 99%
See 1 more Smart Citation
“…Lennon et al (15) reported that MOR promotes opioid-and growth factor-induced proliferation, migration and epithelial-mesenchymal transition in human lung cancer. A recent study confirmed that fentanyl inhibits tumor growth, increases the expression of sirtuin 1 and decreases he expression of acetyl-p65 in colorectal carcinoma cells via the inhibition of NF-κB activation (16). Thus, the potential antitumor activity of fentanyl must be considered in the management of carcinoma pain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have demonstrated that SIRT1 regulated various molecules, including p-53, FOXO1-4, NF-kB, hypermethylated in cancer 1 (HIC1) and E2F1 (17,18). However, the regulatory control of SIRT1 in prostate cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%